Violencia de género desde la perspectiva masculina - Cristobal Quispe , Oscar (2020)
The research was carried out with the aim of knowing the reality of gender violence experienced by men in our society taking into account the masculine perspective and as main actors, men who suffered gender violence, a silent reality that deserves a rethinking in the Peruvian legal system, in such a way that the problem of gender violence can be adequately addressed. The quantitative methodological approach was used, the level of explanatory research and the techniques used were observation, interview, and the survey as a unit of analysis takes into account the men who were victims of violence and who took their cases to the judicial authorities. they have analyzed the judicial files, taking into account the conceptions of violence and gender, together with values and ordinary knowledge and interpretation of the corresponding regulations, also gathering the perspective of the justice operators through an unstructured interview; It is concluded that the reality of gender violence experienced by men in our society constitutes an almost imperceptible problem, since the victims, for the most part, remain silent and / or are ashamed to denounce. This problem is aggravated because, due to their gender status, their protection has not been prioritized or regulated at the legal level.